GEOELECTRIC RESISTIVITY SOUNDING OF RIVERSIDE ALLUVIAL AQUIFER IN AN AGRICULTURAL AREA AT BUYEO, GEUM RIVER WATERSHED, KOREA: AN APPLICATION TO GROUNDWATER CONTAMINATION STUDY - Park Y.-H.; Doh S.-J.; Yun S.-T. (My University, 2007)
Twenty profiles of vertical electric soundings (VES) were obtained in a riverside alluvium at the Buyeo area, South Korea, to examine the variations of subsurface geology and associated groundwater chemistry. The combination of the VES data with the borehole data provided useful information on subsurface hydrogeologic conditions. The vestige of an ancient river channel (e.g. oxbow lake) was identified on the resistivity profiles by the lateral continuation of a near-surface perched aquifer parallel to the river. Such a perched aquifer is typically developed in the area with a clay-rich silty surface alluvium which prohibits the infiltration of oxygen. Therefore, groundwater below the oxbow lake shows a very low nitrate concentration and Eh values under the strong anoxic condition. The distribution of water resistivity is correlated with that of measured total dissolved solids concentration in groundwater, while the earth resistivity of the aquifer shows a significant spatial variation. It is interpreted that the earth resistivity of the aquifer is mainly controlled by the soil type rather than by the water chemistry in the study area. © 2007 Springer-Verlag.
Keywords: AQUIFER GEOLOGY; KOREA; RIVERSIDE ALLUVIUM; SCHLUMBERGER ARRAY; VERTICAL ELECTRIC SOUNDING (VES); WATER CHEMISTRY